Restoring in‐stream habitat in urban catchments: Modify flow or the channel?. Issue 1 (18th October 2018) - Anim, Desmond O.; Fletcher, Tim D.; Vietz, Geoff J.; Pasternack, Gregory B.; Burns, Matthew J.
Abstract: Urban streams have almost universally altered physical habitat conditions due to excess stormwater run‐off. This includes changes to in‐channel hydraulics and channel morphology. Restoration of in‐channel habitat has two main levers: address the hydrology or channel morphology. Both variables impact in‐stream habitat, but understanding the relative role of hydrologic and morphologic change remains a challenge. This study uses two‐dimensional hydraulic modelling to examine the relative roles of flow and channel morphology in setting hydraulic conditions. We investigated four test scenarios involving the combinations of urban versus natural hydrology and urban versus natural channel morphology. The analysis investigated three ecologically relevant hydraulics characteristics: bed mobilization, retentive habitat, and floodplain inundation, using Shields stress, shallow slow‐water habitat (SSWH) area, and floodplain inundation area hydraulic metrics, respectively. The results indicate substantial differences in hydraulic conditions between the two reaches. The urban reach showed increased bed mobility potential and SSWH availability plummeted as flow increased, whereas the natural channel showed a relatively stable bed with substantially more SSWH at most flows. Floodplain inundation frequency was low in the urban channel with decreased duration. Scenarios examined suggest that hydraulic conditions are highly sensitive to channel morphology relative to flow regime. This suggests that once channel form has been degraded, mitigating urbanization impacts on flow regime cannot maintain "natural" channel hydraulics. Management approaches therefore must protect channel morphology from change. Where the channel has already been fundamentally altered, opportunities for channel morphology rehabilitation need to be considered.